Improving the Communication of Dental Findings in Pediatric Dentistry by Using Intraoral Scans as a Visual Aid: A Randomized Clinical Trial - Nelly Schulz-Weidner; Marina Gruber; Eva May Schraml; Bernd Wöstmann; Norbert Krämer; Maximiliane Amelie Schlenz (Dentistry Journal, 2024)
The aim of this first randomized clinical trial (RCT) was to determine whether intraoral scans (IOS) can be used as a visual aid to improve the communication of dental findings in pediatric dentistry. Therefore, 60 children (mean age 10.1 ± 3.3 years) and their accompanying parents/primary caregivers (PGs) were examined between July 2022 and February 2023. Patients were randomly allocated to two groups: half of the participants were informed of the children’s dental findings including treatment plans by verbal explanation alone (control group, n = 30), while the other half were informed using IOS (Trios 4, 3Shape) as a visual aid to support the verbal explanation (study group, n = 30). Both groups then completed a questionnaire regarding their children’s diagnosis, treatment needs, planned therapy, and oral hygiene. Statistical analysis was performed using a t-test (p < 0.05). Overall, there was a significant difference between the two groups (p < 0.001) in terms of understanding the current oral situation of their children. While 85.5 ± 17.3% (mean ± standard deviation) of the answers were correct in the study group, only 57.2 ± 17.8% of the participants in the control group were capable of answering the questions correctly. In particular, the control group had difficulties answering the questions about treatment needs and therapy correctly. Within the limitations of this first pilot study, IOS can be clearly recommended as a visual aid to improve the communication of dental findings with PGs in pediatric dentistry.